Controls on the behaviors of rare earth elements in acidic and alkaline thermal springs. (August 2022) - Li, Bo; Kong, Qingmin; Wang, Guangcai; Liu, Fei; Guo, Liang; Liu, Chenglong; Liao, Fu; Shi, Zheming
Abstract: Understanding the rare earth elements (REE) behaviors in aquatic environment is important to reveal the complex hydrochemical processes and hydrological circulation, such as water-rock interactions, mixing, redox reactions. Based on the samples collected from the Rehai geothermal field, southwestern China and the data from published literature, this study revealed that there are apparently differences in general hydrochemistry and REE geochemistry characteristics between the acidic and alkaline springs. The content of REE in acidic springs is one to three orders of magnitude higher than that of alkaline springs and river water. The NASC-normalized REE patterns of acidic springs are more similar to river water and volcanic rocks, but heavy rare earth elements (HREE) in all samples are enriched compared with volcanic rocks. Moreover, the most remarkable characteristic is that the total concentration of REE decreases significantly with the increase in pH of the springs, but rises slightly after water becomes neutral. Through speciation calculations, major REE species are Ln 3+ and LnSO4 + in acidic springs (Ln represents REE), and REE hydroxide complexes are predominant in alkaline springs. The behaviors of REE in thermal springs are controlled by three processes: (i) the dissolution and alteration of primary minerals containing REE vary with the pH of water. The co-alteration of the whole-rock minerals contribute to the REE in the acidic springs, whereas the dissolution of feldspar is main source of REE in the alkaline springs; (ii) the content and species of Fe and Mn affects the adsorption, desorption and co-precipitation of REE, especially under weakly alkaline conditions; and (iii) inorganic complexation and adsorption are responsible for the fractionation between LREE and HREE. The positive Eu anomaly is mainly owing to preferential dissolution of feldspar in alkaline springs. Combined with the general hydrochemistry of thermal springs, isotopic data and inverse geochemical modeling, acidic springs in the Rehai geothermal field generate from oxidized shallow water heated by steam containing H2 S, and alkaline springs are derived from deep geothermal water. Highlights: The acidic and alkaline springs possess different REE content and partition patterns. The REE in acidic springs originate from co-alteration of whole rock under low pH. Dissolution of feldspar and co-precipitation control REE content in alkaline springs. The REE fractionation is induced by difference in adsorption of REE complexes.